Paradigma Inisiasi Kultural Ke Multikulturalisme - Putu Yulia Angga Dewi (Purwadita : Jurnal Agama dan Budaya, 2020)
Indonesia is a multicultural country with a very diverse number of ethnicities, cultures, languages, religions, and backgrounds. But unfortunately, the awareness of multiculturalism in our society has not yet developed properly. Education is a solution to unravel the tangled thread of prolonged conflict thanks to its role as social reconstruction. Implementation of multicultural education that emphasizes the importance of awareness of differences requires commitment from all elements of society because it requires reform of the education paradigm.Keywords: Cultural, Multiculturalism